2015
DOI: 10.7227/jace.21.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Iraqi Adult Learners: Experiences of Spoken Register in English for Academic Purposes Programs at an Australian University

Abstract: This paper explores the perceptions of Iraqi students of three different English Programs (a general English for academic purposes program, a pre-enrolment English program and the English component of a disciplinary bridging program) at an Australian University as reflected in their language learning narratives. It focuses specifically on the students' experience of academic spoken register in the aforementioned programs and how their experiences are affected by Australian English higher education policies. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Despite this, narrative inquiry is well-suited to address issues of complexity and human centeredness because of its capacity to record and retell events that have been of most influence on us. The use of narratives as data has gained acceptance across a range of disciplines, including education (see Tsui, 2007; Zeek, Foote, & Walker, 2001), and has found a place within the fields of adult education (see Al Hamdany, & Picard, 2015; Daniels, 2008; Gola, 2009; Misawa, 2014) and HRD (see Pettersson, Bolander Laksov, & Fjellström, 2015).…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…Despite this, narrative inquiry is well-suited to address issues of complexity and human centeredness because of its capacity to record and retell events that have been of most influence on us. The use of narratives as data has gained acceptance across a range of disciplines, including education (see Tsui, 2007; Zeek, Foote, & Walker, 2001), and has found a place within the fields of adult education (see Al Hamdany, & Picard, 2015; Daniels, 2008; Gola, 2009; Misawa, 2014) and HRD (see Pettersson, Bolander Laksov, & Fjellström, 2015).…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…At the university level, English is viewed as essential for both undergraduate and postgraduate studies in most Science, Technology Engineering, Mathematics and Medicine (STEMM) disciplines where some subjects are even taught through the medium of English, (Al Hamdany & Picard, 2013). However, there are still various pedagogical and practical challenges such as an absence of English native speakers to communicate with (Al Hamdany & Picard, 2014) and outdated teacher-centered teaching methods (Alseady, 2017). Ali's (2012) study showed that while grammatical structures were scaffolded to a certain extent, scaffolding of context and register was lacking.…”
Section: Introductionmentioning
confidence: 99%